A mid-ranging control strategy for non-stationary processes and its application to dissolved oxygen control in a bioprocess. (September 2015) - Johnsson, O.; Sahlin, D.; Linde, J.; Lidén, G.; Hägglund, T.
Abstract: In this study a modified mid-ranging strategy is proposed where the controller for the secondary manipulated variable uses its own output as its setpoint, possibly with an offset and/or re-scaling. This modification allows the manipulated variables to increase in unison so that the mid-ranging advantage of utilizing the fast dynamics of the primary controller to regulate the process can be achieved also in non-stationary processes, while not adding complexity to the controller. The proposed control strategy has been implemented in pilot-scale (500 l) industrial bioprocesses where it is used to control the dissolved oxygen level by manipulating agitator speed and aeration rate. The controller is demonstrated to perform well in these, outperforming a reference controller which has previously been shown to give satisfactory control performance. It is also shown in similar experiments that the strategy can easily be adapted to control dissolved oxygen in bioprocesses where the feed rate is controlled using an extremum-seeking controller. The proposed strategy is generally applicable to non-stationary processes where a mid-ranging approach is suitable. Abstract : Highlights: A modification to the mid-ranging control architecture which enables its use in non-stationary processes is presented. The modification does not add to the complexity of the control architecture. Experimental results demonstrating the successful use of the controller and comparison to a previously used method are provided.